Mr. Cavendish, I presume - Quinn, Julia (New York : Avon, 2008)
Engaged to the future Duke of Wyndham since she was just six months old, Amelia Willoughby is beginning to get tired of waiting for Thomas Cavendish. His world is rocked by the arrival of his long-lost cousin, who may or may not be the true Duke of Wyndham. And if Thomas is not the duke, then he's not engaged to Amelia.
Keywords: Nobility -- Fiction; Marriage -- Fiction; Cousins -- Fiction; Regency fiction; Love stories